A descriptive analysis of HIV prevalence, HIV service uptake, and HIV-related risk behaviour among patients attending a mental health clinic in Rural Malawi. - Kinke Lommerse; Robert C Stewart; Queen Chilimba; Thomas van den Akker; Crick Lund (PLoS ONE, 2013)
BACKGROUND: Human immunodeficiency virus (HIV) and mental illness are interlinked health problems; mental illness may pose a risk for contracting HIV and HIV-positive individuals are at higher risk of mental illness. However, in countries with high HIV prevalence, the main focus of HIV-related health programmes is usually on prevention and treatment of somatic complications of HIV, and mental illness is not given high priority. We examined HIV prevalence, uptake of HIV services, and HIV-related risk behaviour among people attending a mental health clinic in rural Malawi. METHODOLOGY: Semi-structured interviews were performed with patients capable to consent (94%), and with those accompanied by a capable caregiver who consented. HIV counselling and testing was offered to participants. FINDINGS: Among 174 participants, we collected 162 HIV test results (91%). HIV prevalence was 14.8%. Women were three times as likely to be HIV-positive compared to men. Two-thirds of participants reported having been tested for HIV prior to this study. The uptake of HIV-services among HIV-positive patients was low: 35% did not use recommended prophylactic therapy and 44% of patients not receiving antiretroviral treatment (ART) had never been assessed for ART eligibility. The reported rate of sexual activity was 61%, and 9% of sexually active participants had multiple partners. Inconsistent condom use with stable (89%) and occasional (79%) sexual partners, and absence of knowledge of the HIV status of those partners (53%, 63%) indicate high levels of sexual risk behaviour. CONCLUSIONS: HIV-prevalence among persons attending the clinic, particularly men, was lower than among the general population in a population survey. The rate of HIV testing was high, but there was low uptake of preventive measures and ART. This illustrates that HIV-positive individuals with mental illness or epilepsy constitute a vulnerable population. HIV programmes should include those with neuropsychiatric illness.